Mid‐term trends and recent birth‐cohort‐dependent changes in incidence rates of cutaneous malignant melanoma in Italy. Issue 4 (28th August 2020) - Bucchi, Lauro; Mancini, Silvia; Crocetti, Emanuele; Dal Maso, Luigino; Baldacchini, Flavia; Vattiato, Rosa; Giuliani, Orietta; Ravaioli, Alessandra; Caldarella, Adele; Carrozzi, Giuliano; Ferretti, Stefano; Filiberti, Rosa Angela; et al.
Abstract: In Oceania, North America and north‐western Europe, after decades of increase, cutaneous malignant melanoma (CMM) rates began to stabilise or decline before 2000. Anecdotal evidence suggests that the reversal of the incidence trend is extending to southern Europe. To obtain a formal confirmation, this nationwide study from Italy investigated the incidence trends by birth cohort. Twenty‐one local cancer registries covering a population of 15 814 455 provided incidence data for primary CMM registered between 1994 and 2013. Trends in age‐standardised rates were analysed using joinpoint regression models and age‐period‐cohort models. Age‐standardised incidence showed a consistent increase throughout the period (estimated annual percent change, 3.6 [95% confidence interval, 3.2‐4.0] among men and 2.5 [2.0‐3.1] among women). This pattern was confirmed by a sensitivity analysis with removal of low‐risk populations of southern Italy. The rates, however, showed a stabilisation or a decrease in men and women aged below 35. Using the cohort of 1949—the median cohort with respect to the number of cases for both genders—as a reference, the incidence rate ratio increased for successive cohorts born until 1973 (women) and 1975 (men), and subsequently tended to decline. For the most recent cohorts in both genders, the risk of disease returned to the level of the cohort of 1949. The changes observed in the latest generations can be interpreted as the earliest manifestations of a birth‐cohort‐dependent incidence decrease. Our study adds to previous data indicating that the reversal of the long‐term upward incidence trend of CMM is extending to southern Europe. Abstract : What's new? After increasing for many years, malignant melanoma rates began to stabilise or decline in many regions before 2000. Is this also true for southern Europe? In the current study, the authors found that melanoma rates have also began to decline in Italy. The reversal of the long‐term, worldwide increase in melanoma risk seen in other Caucasian populations thus appears to extend to southern Europe. These results indicate that primary prevention strategies have been effective in modifying sun‐exposure habits in this region, and should continue to be reinforced via public health messaging.